Temporal patterns of macrophage‐ and neutrophil‐related markers are associated with clinical outcome in heart failure patients - Dominika Klimczak‐Tomaniak; Elke Bouwens; Anne‐Sophie Schuurman; K. Martijn Akkerhuis; Alina Constantinescu; Jasper Brugts; B. Daan Westenbrink; Jan vanRamshorst; Tjeerd Germans; Leszek Pączek; Victor Umans; Eric Boersma; et al. (ESC Heart Failure)
Abstract Aims Evidence on the association of macrophage‐ and neutrophil‐related blood biomarkers with clinical outcome in heart failure patients is limited, and, with the exception of C‐reactive protein, no data exist on their temporal evolution. We aimed to investigate whether temporal patterns of these biomarkers are related to clinical outcome in patients with stable chronic heart failure (CHF). Methods and Results In 263 patients with CHF, we performed serial plasma measurements of scavenger receptor cysteine‐rich type 1 protein M130 (CD163), tartrate‐resistant acid phosphatase type 5 (TRAP), granulins (GRN), spondin‐1 (SPON1), peptidoglycan recognition protein 1 (PGLYRP1), and tissue factor pathway inhibitor (TFPI). The Cardiovascular Panel III (Olink Proteomics AB, Uppsala, Sweden) was used. During 2.2 years of follow‐up, we collected 1984 samples before the occurrence of the composite primary endpoint (PE) or censoring. For efficiency, we selected 567 samples for the measurements (all baseline samples, the last two samples preceding the PE, and the last sample before censoring in event‐free patients). The relationship between repeatedly measured biomarker levels and the PE was evaluated by joint models. Mean (±standard deviation) age was 67 ± 13 years; 189 (72%) were men; left ventricular ejection fraction (%) was 32 ± 11. During follow‐up, 70 (27%) patients experienced the PE. Serially measured biomarkers predicted the PE in a multivariable model adjusted for baseline clinical characteristics [hazard ratio (95% confidence interval) per 1‐standard deviation change in biomarker]: CD163 [2.07(1.47–2.98), P < 0.001], TRAP [0.62 (0.43–0.90), P = 0.009], GRN [2.46 (1.64–3.84), P < 0.001], SPON1 [3.94 (2.50–6.50), P < 0.001], and PGLYRP1 [1.62 (1.14–2.31), P = 0.006]. Conclusions Changes in plasma levels of CD163, TRAP, GRN, SPON1, and PGLYRP1 precede adverse cardiovascular events in patients with CHF.